2018
DOI: 10.12968/jowc.2018.27.5.320
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of antimicrobial activity of selected, commercially available wound dressing materials

Abstract: Some important differences in the antimicrobial potential of investigated materials have been found. The presented results could be of interest to clinicians managing wounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 37 publications
1
11
0
1
Order By: Relevance
“…By contrast, MH, made from the nectar of the manuka bush (Leptospermum scoparium), remains active after catalase treatment and is effective at low concentrations, and is therefore much more effective as an antimicrobial agent (Molan and Russell 2015). Manuka honey has proven effective at both the treatment and prevention of growth of multi-drug resistant bacteria (Jenkins et al 2011a), fungi (Irish et al 2006) and biofilms (Maddocks et al 2012); this has made it a suitable alternative to common antimicrobial treatments, especially in wound care (Guthrie et al 2014;Abd El-Malek et al 2017;Watson et al 2017;Hussain 2018;Szweda et al 2018). There are many factors contributing to the antimicrobial activity of MH, including low pH, high osmolarity and the presence of phytochemicals (Mandal and Mandal 2011).…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, MH, made from the nectar of the manuka bush (Leptospermum scoparium), remains active after catalase treatment and is effective at low concentrations, and is therefore much more effective as an antimicrobial agent (Molan and Russell 2015). Manuka honey has proven effective at both the treatment and prevention of growth of multi-drug resistant bacteria (Jenkins et al 2011a), fungi (Irish et al 2006) and biofilms (Maddocks et al 2012); this has made it a suitable alternative to common antimicrobial treatments, especially in wound care (Guthrie et al 2014;Abd El-Malek et al 2017;Watson et al 2017;Hussain 2018;Szweda et al 2018). There are many factors contributing to the antimicrobial activity of MH, including low pH, high osmolarity and the presence of phytochemicals (Mandal and Mandal 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, both CMC and plasma-treated PCL possess high fluid absorption capacity. As a result, when the dressings absorb fluid and swell, bacteria available in the MH medium might be trapped inside their polymer matrix, leading to the reduction in bacteria colonies remained after being collected between 0 h and 1 h. On the other hand, even though PCLGelAg expressed a slower speed of kill against S. aureus , the dressing was able to reach maximal killing rate after 12 h of bacteria exposure and sustain the effect for at least 24 h. Indeed, the antimicrobial activity is further affected by the diverse silver species [ 42 ], which are in charge of the interaction with bacteria, and base materials, which manage the silver released duration and concentration [ 37 ]. Combining with the data from the agar diffusion assay and microdilution method, it is suggested that PCLGelAg should be used topically and changed daily to maintain the highest bactericidal performance.…”
Section: Discussionmentioning
confidence: 99%
“…In "in vitro" studies from 2015, 2017, and 2018, it was shown that Mepilex® Ag was highly effective against some of the most common bacterial pathogens in burns, such as staphylococcus aureus and pseudomonas aeruginosa [115][116][117]. However, it has also shown to have a negative effect on cell survival [115,118].…”
Section: Cytotoxicity Of Mepilex®agmentioning
confidence: 99%